PO.6.132 A phase 2b study of afimetoran (BMS-986256) in patients with active systemic lupus erythematosus (SLE): optimization of a lupus clinical trial design. (27th September 2022) - Ranganathan, U; Merrill, JT; Crow, MK; Delev, N; Banerjee, S; Grasela, D; Harrison, M; Shen, Y; Culotta, E; Greenberg, S; Shah, V
Abstract : Purpose: Activation of toll-like receptor (TLR)7/8 by self-RNA induces production of type I interferon and several other proinflammatory cytokines, which may contribute to the pathophysiology of SLE and other related autoimmune diseases. Afimetoran, a potent, selective, oral small-molecule inhibitor of TLR7/8, was developed for potential treatment of autoimmune diseases and has shown robust efficacy and improved survival in murine models of established and advanced lupus (Dudhgaonkar et al. ACR Convergence 2021. Abstract 0470). In healthy volunteers, afimetoran demonstrated favorable pharmacologic and safety profiles (Harrison et al. ACR Convergence 2021. Abstract 1771). These results suggest afimetoran may offer a novel therapeutic approach for the treatment of patients with SLE. Applying lessons from previous clinical studies, we optimized a clinical trial design to determine whether TLR7/8 inhibition with afimetoran leads to clinical improvement in SLE disease activity. Methods: Approximately 344 patients with active SLE on standard medications are being randomized 1:1:1:1 to receive oral afimetoran dose level (DL) 1, DL2, DL3, or placebo once daily for 48 weeks ( Figure 1 ). The primary endpoint is response rate per the SLE Responder Index (SRI[4]) at Week 48. Secondary endpoints include SRI(4) response with corticosteroid (CS) reduction and maintenance to ≤ 7.5 mg per day, British Isles Lupus Assessment Group-based Composite Lupus Assessment response, reduction in Cutaneous Lupus Erythematosus Disease Area and Severity Index scores, reduction in counts of swollen and tender joints, patient-reported outcomes, and afimetoran safety and tolerability. Results: Lessons learned from failed clinical trials and best practices from recent successful trials are being adopted in this study. This study includes modified eligibility criteria, requiring adequate disease severity to ensure observed improvements are clinically meaningful ( Figure 1 ), tapering of CS therapy to reduce placebo responses, and ongoing review by a panel of lupus trial experts to ensure accuracy and consistency of patient data. Conclusions: Afimetoran is a novel, oral, potent, selective inhibitor of TLR 7/8. Using insights from past lupus clinical trial designs, a phase 2b clinical trial design was optimized to test whether inhibition of TLR7/8 is beneficial for the treatment of SLE. This study is currently enrolling patients globally (EudraCT 2019–004021-25; NCT04895696 ).